Imaging, Behavior and Endocrine Analysis of “Jealousy” in a Monogamous Primate - Maninger, Nicole; Mendoza, Sally P.; Williams, Donald R.; Mason, William A.; Cherry, Simon R.; Rowland, Douglas J.; Schaefer, Thomas; Bales, Karen L. (Frontiers in Ecology and Evolution, 2017)
Understanding the neurobiology of social bonding in non-human primates is a critical step in understanding the evolution of monogamy, as well as understanding the neural substrates for emotion and behavior. Coppery titi monkeys (Callicebus cupreus) form strong pair bonds, characterized by selective preference for their pair mate, mate-guarding, physiological and behavioral agitation upon separation, and social buffering. Mate-guarding, or the “maintenance” phase of pair bonding, is relatively under-studied in primates. In the current study, we used functional imaging to examine how male titi monkeys viewing their pair mate in close proximity to a stranger male would change regional cerebral glucose metabolism. We predicted that this situation would challenge the pair bond and induce “jealousy” in the males. Animals were injected with [18F]-fluorodeoxyglucose (FDG), returned to their cage for 30 min of conscious uptake, placed under anesthesia, and then scanned for 1 hour on a microPET P4 scanner. During the FDG uptake, males (n=8) had a view of either their female pair mate next to a stranger male (“jealousy” condition) or a stranger female next to a stranger male (control condition). Blood and cerebrospinal fluid samples were collected and assayed for testosterone, cortisol, oxytocin, and vasopressin. Positron emission tomography (PET) was co-registered with structural magnetic resonance imaging (MRI), and region of interest analysis was carried out. Bayesian multivariate multilevel analyses found that the right lateral septum (Pr(b>0)=93%), left posterior cingulate cortex (Pr(b>0)=99%), and left anterior cingulate (Pr(b>0)=96%) showed higher FDG uptake in the jealousy condition compared to the control condition, while the right medial amygdala (Pr(b>0)=85%) showed lower FDG uptake. Plasma testosterone and cortisol concentrations were higher during the jealousy condition. During the jealousy condition, duration of time spent looking across at the pair mate next to a stranger male was associated with higher plasma cortisol concentrations. The lateral septum has been shown to be involved in mate-guarding and mating-induced aggression in monogamous rodents, while the cingulate cortex has been linked to territoriality. These neural and physiological changes may underpin the emotion of jealousy, which can act in a monogamous species to preserve the long-term integrity of the pair.